The Effect of Using E-modules in Mathematics Subjects on Increasing Concept Understanding and Critical Thinking - Haziza, Haziza; Sumiharsono, Rudy; Triwahyuni, Eges (STAI Miftahul Ula Nganjuk, 2023)
This study aims to determine the influence of the discovery learning model on learning activities and student learning outcomes. The problems studied in this study are: 1) Is there any effect of using E-modules on increasing conceptual understanding in students? 2) Is there any effect of using E-modules on improving Critical Thinking in students. 3) Is there any effect of using E-modules on improving conceptual understanding and critical thinking in students together? The design of this study was quantitatively causal. The data collection method uses questionnaires, tests, and documentation. Data analysis was carried out with validity and reliability tests, classical assumption tests in the form of normality tests, multicollinearity tests, autocorrelation tests, heteroscedasticity tests, and hypothesis testing with F tests. The results showed that (1) there was an influence of the use of E-modules on increasing understanding of concepts by showing a calculated t value of 1.842 greater than t table (2) the effect of using E-modules on critical thinking by showing a calculated t value of 2.275 greater than t table (3) the results of regression analysis obtained f count 4.494 greater than f table, then there was an influence of using E-modules on increasing concept understanding and critical thinking together.